Tinjauan Terhadap Proses Klaim Asuransi Jiwa Kumpulan Pada PT. Asuransi Syariah Keluarga Indonesia - Rian Hasanah; Ikhwan Hamdani; Hilman Hakiem (Ekonomi Islam, 2018)
This research aims to determine how the claims process of life insurance group at PT. Asuransi Syariah Keluarga Indonesia and the cause of postponed and rejected claims. Type of the research used descriptive qualitative research. The result of the research showed that in general there are four claims process, notification process, evidence of claim document, claim investigation and claim settlement. Those four processes that PT. Asuransi Syariah Keluarga Indonesia applied are simple and easy. The claim investigation conducted if at the time of verification found irrelevant data. The cause of the postpone claims is the lack of documents that the institution gave to the insurance company, so the claim must be postponed until the file is completed at a predetermined time. The cause of the claim being rejected is the policy status is not active, the participant is not a member, contravene "utmost good faith” principle, etc. Keyword: Life Insurance Group, Process, Claims.